Role of human relations in training organizations - Jahanian, Ramezan (2014)
Human is created social that have to leave and communicate. These communications are wide spread.Children education and family management required to intimate relationship.For working in the factories, Schools or hospitals, we need to communicate whit managements and co workers.Reflex ion and language are two man advantage that cause to create idea, culture and civilization, that we can translate these, just with communication.Just man can pray with organized process and to self creator with communicative language like prayer and orison and say self needs to him.Working and in new organization open the new horizon for man.Although the huge developments in different areas, Man are also the major pieces of organization as organizations success for making their objects depends on how they think about man and how apply this forces with creation of man relationship, was clarified that classical theories know man important just of economical and the workers like machines that must use them as a mechanical energy for developing of production level, they don’t have any important and effective in working out put developing and organization production level, but we can derive with are effective on man’s organizational behavior and effect in redacting or increasing of output and production by man relationship.Man interesting and participating in objects determination, reinforce their plans and moral and commute to implement the best participatory management is objective management.Human behavior causes based on developments and political, social and cultural transitions and the basic theory about human behavior is that must confirm mental and social behavior of person or work group.Studies about human relationship proved that organization are concluding social and emotional aspect, except of economical aspects.Hath urn’s experiences showed that respect to man as human and attention to informal organization is as important as formal organization and physical – economical work condition for efficiency.